2018
DOI: 10.1080/00952990.2018.1436179
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging user perspectives for insight into cannabis concentrates

Abstract: Continued research on concentrates use in the US is needed. Research-informed policies that foster safe and responsible use of concentrates are necessary to protect users, especially those who use concentrates frequently, from potential negative side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…7,13,14,[17][18][19]21,35,42,43 Moreover, adolescent cannabis users may be more vulnerable to these effects than adult cannabis users. [37][38][39] Finally, adverse acute consequences of concentrate use, such as loss of consciousness and burn injuries, 15,27,28,41,44 might be more likely among infrequent users, who comprise the majority of adolescent users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,13,14,[17][18][19]21,35,42,43 Moreover, adolescent cannabis users may be more vulnerable to these effects than adult cannabis users. [37][38][39] Finally, adverse acute consequences of concentrate use, such as loss of consciousness and burn injuries, 15,27,28,41,44 might be more likely among infrequent users, who comprise the majority of adolescent users.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] Adolescent cannabis users' use of concentrates, specifically, might further amplify their risk for cannabis use disorder and adverse cannabis-related consequences; studies of adult cannabis users have suggested that use of concentrates and use of marijuana with higher versus lower THC content are associated with more severe cannabis dependence, 7,13,19,21,35 greater risk of psychosis, 17,18,40 and greater cannabis-related differences in brain structure. 20 Moreover, use of cannabis with higher THC content may cause more severe acute effects, such as altered reality and loss of consciousness, 15,28,32,[41][42][43] and the production and use of solvent-based concentrates are associated with increased risk of explosions and burns. 27,44 These severe acute consequences might be especially likely among inexperienced cannabis users, 16 who comprise the majority of adolescents who use cannabis.…”
mentioning
confidence: 99%
“…E-liquids with flavoring can be used to mask the odor of cannabis and make it less detectable [54]. Many of cannabis extracts (oils, vape cartridges, hash) that are vaporized can contain 60% THC, with solid extracts such as wax, budder, shatter, or crumble can exceed 90% [55,56]. Any of these extracts can be vaporized through an electronic delivery system and e-cigarettes.…”
Section: Smoking and Vaping (Aerosolization)mentioning
confidence: 99%
“…In this regard, Palamar et al [17] point out that with legalization, marijuana consumption may increase due to an increase in the acceptability of this substance and a decrease in the perception of its danger, causing, in turn, a significant increase in the number of individuals who drive under the influence of cannabis. Regarding causality, Cavazos-Rehg et al [18] argue that the risk of an accident is not a direct cause of legalization, since the decision to drive under the influence of cannabis is a purely individual act.…”
Section: Introductionmentioning
confidence: 99%